Japan Obstetric Compensation System for Cerebral Palsy: Strategic system of data aggregation, investigation, amelioration and no‐fault compensation. Issue 3 (22nd January 2019) - Ushiro, Shin; Suzuki, Hideaki; Ueda, Shigeru
Abstract: The Japan Obstetric Compensation System for Cerebral Palsy (JOCS‐CP), which investigates, develops preventive mechanisms and awards monetary compensation, to cases of cerebral palsy was urgently introduced in 2009 in response to growing concern about Japan's deteriorating perinatal care and low birthrate. Under the political leadership, the Japan Council for Quality Health Care launched the JOCS‐CP with support of various stakeholders. The JOCS‐CP features of no‐fault‐based compensation which was discussed decades ago in the Japan Medical Association aiming at financial aid to patient and family and early settlement of dispute. As of 2017, 2233 petitions had been approved by the Review Committee for compensation. All the approved cases were consecutively put on analysis in the Investigation Committee which has compiled more than 1000 Investigative Reports. The reports were delivered not only to the childbirth facility but to the guardians/families. Survey revealed that most of childbirth facility and the guardians/families responded in favor of the reports. With regard to amelioration of profound cerebral palsy, the Prevention Report has been published on annual basis through analysis of all the Investigative Reports. The Prevention Reports and other educational materials were produced and distributed not only among medical professionals but among pregnant women. It is notable that the number of lawsuit filing related to obstetrics demonstrated rapid decrease compared to that of other medical specialties. The JOCS‐CP could be described as a social experiment. It was overhauled in 2015 but deserves further discussion on reform for evolving into better system.